Iridium catalyst composite proton membrane and preparation method and application thereof

By forming an iridium catalyst in situ on the surface of the proton membrane, the problem of insufficient binding force between the iridium catalyst and the proton membrane is solved, the performance and life of the electrolytic cell are improved, and the stability and efficient combination of the iridium catalyst are achieved.

CN119392306APending Publication Date: 2025-02-07GUANGDONG ENERGY GROUP SCIENCE & TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531660.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the binding force between the iridium catalyst and the proton membrane is insufficient, resulting in the catalyst falling off, affecting the performance and life of the electrolytic cell electrode.

Method used

By mixing the pretreated proton membrane with the iridium source solution, after heating, and then mixing it with the reducing agent solution, performing two-step heating treatment to form an iridium catalyst composite proton membrane in situ, thereby increasing the binding force between the iridium catalyst and the proton membrane.

Benefits of technology

The close combination of the iridium catalyst and the proton membrane is achieved, the performance and life of the electrolytic cell are improved, and the stability and difficulty of the iridium catalyst are ensured.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an iridium catalyst composite proton membrane as well as a preparation method and application thereof, and the preparation method comprises the following steps: (1) sequentially performing hydrogen peroxide treatment and sulfuric acid treatment on a proton membrane to obtain a pretreated proton membrane; (2) adjusting the pH value of an iridium source solution, mixing the pretreated proton membrane with the iridium source solution, and carrying out one-step heating treatment to obtain a precursor; and (3) mixing the precursor with a reducing agent solution, and carrying out two-step heating treatment to obtain the iridium catalyst composite proton membrane. The iridium catalyst is prepared on the surface of the proton membrane in situ through a simple method, and the iridium catalyst is tightly combined with the proton membrane, high in stability and not prone to falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and relates to an iridium catalyst composite proton membrane and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy technologies, hydrogen production by water electrolysis, especially pure water electrolysis, has been increasingly valued due to its huge advantages. In pure water electrolysis for hydrogen production, the performance of the electrolyzer mainly depends on the performance of the electrolyzer electrodes. In the field of pure water electrolysis for hydrogen production, most of them use proton membranes as carriers, attach catalysts with high catalytic performance to the surface of proton membranes, and make electrolyzer electrodes with the function of electrolyzing pure water. The performance of the catalyst is closely related to the performance of the electrolyzer electrodes. At present, the mainstream commercial electrolyzer electrodes are made by the catalyst coating membrane method (CCM), which is to spray the catalyst on the surface of the proton membrane to form a thinner electrolyzer electrode.

[0003] During the hydrogen production process by electrolysis of water, the hydrogen and oxygen produced by electrolysis are precipitated from the cathode and anode surfaces of the electrolyzer electrodes respectively, which will have a scouring effect on the catalyst on the surface of the electrolyzer electrodes, reduce the binding force between the catalyst and the proton membrane, cause the catalyst to fall off, and affect the performance and life of the electrolyzer electrodes.

[0004] The main components of the catalyst in the electrolytic cell electrode are platinum and iridium catalysts, and the performance of the electrolytic cell electrode depends largely on the iridium catalyst. Therefore, increasing the binding force between the iridium catalyst and the proton membrane will greatly improve the performance and life of the electrolytic cell electrode.

[0005] CN118619376A discloses iridium oxide, a preparation method thereof and an application thereof in an anode catalyst for producing hydrogen by electrolysis of water. The preparation method of iridium oxide comprises the following steps: (1) dissolving conductive carbon black in a solvent to form a carbon suspension and adjusting the pH; (2) adding an iridium precursor and a surfactant to the carbon suspension and mixing them; (3) removing the solvent; and (4) performing high-temperature heat treatment to obtain iridium oxide.

[0006] CN118480808A discloses a membrane electrode preparation method and a membrane electrode thereof, comprising: preparing a proton exchange membrane electrolysis hydrogen production anode slurry; adding nano platinum wires to the anode slurry and mixing to form a mixed slurry; coating the mixed slurry on the proton exchange membrane or the transfer membrane, drying the mixed slurry coated on the proton exchange membrane to form a membrane electrode, and thermally transferring the catalyst layer coated on the transfer membrane to form a membrane electrode. The components of the anode slurry include iridium oxide catalyst, ionomer, solvent water and isopropanol solvent.

[0007] The above scheme prepares the iridium catalyst separately and coats it on the proton exchange membrane in the form of slurry. The combination of the two is not ideal. It is relatively difficult to deposit iridium on the surface of the proton membrane by chemical methods. The main problem is that the iridium ion is difficult to reduce, and during the reduction process, the reduced iridium is difficult to adhere to the surface of the proton membrane, resulting in a very low iridium content in the electrolytic cell electrode, which leads to poor electrolytic performance. Summary of the invention

[0008] The purpose of the present invention is to provide an iridium catalyst composite proton membrane and a preparation method and application thereof. The present invention uses a simple method to in-situ prepare an iridium catalyst on the surface of the proton membrane. The iridium catalyst is tightly combined with the proton membrane, has high stability, is not easy to fall off, and greatly improves the performance level and life of the electrolytic cell.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing an iridium catalyst composite proton membrane, the preparation method comprising the following steps:

[0011] (1) treating the proton membrane with hydrogen peroxide and sulfuric acid in sequence to obtain a pretreated proton membrane;

[0012] (2) after adjusting the pH of the iridium source solution, mixing the pretreated proton membrane with the iridium source solution, and subjecting the mixture to a one-step heating treatment to obtain a precursor;

[0013] (3) The precursor is mixed with a reducing agent solution, and subjected to a two-step heating treatment to obtain the iridium catalyst composite proton membrane.

[0014] The present invention places the proton membrane treated with hydrogen peroxide and sulfuric acid into a prepared iridium source solution for reaction, and then places the proton membrane after the iridium source solution reaction into a sodium borohydride solution, and an iridium catalyst is deposited in situ on the surface of the proton membrane. In the iridium catalyst composite proton membrane prepared by the method of the present invention, the iridium catalyst is in situ formed on the surface of the proton membrane, and the iridium catalyst is tightly combined with the proton membrane, is not easy to fall off, and has high stability.

[0015] Preferably, the proton membrane in step (1) comprises any one of perfluorosulfonic acid proton exchange membrane, Nafion recast membrane, non-fluorinated polymer proton exchange membrane or novel composite proton exchange membrane, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of perfluorosulfonic acid proton exchange membrane and novel composite proton exchange membrane, a combination of non-fluorinated polymer proton exchange membrane and novel composite proton exchange membrane, or a combination of perfluorosulfonic acid proton exchange membrane and Nafion recast membrane.

[0016] Preferably, the mass concentration of the hydrogen peroxide in step (1) is 3% to 8%, for example, 3%, 4%, 5%, 6%, 7% or 8%, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] Preferably, the concentration of sulfuric acid in step (1) is 0.2 mol / L to 1 mol / L, for example, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L or 1 mol / L, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Preferably, the concentration of iridium ions in the iridium source solution in step (2) is 0.02mol / L to 0.2mol / L, for example: 0.02mol / L, 0.05mol / L, 0.1mol / L, 0.15mol / L or 0.2mol / L, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the solute of the iridium source solution in step (2) includes iridium trichloride.

[0020] Preferably, the solvent of the iridium source solution in step (2) comprises methanol and water.

[0021] Preferably, the volume ratio of methanol to water is 1:(10-15), for example 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the pH in step (2) is ≥7.

[0023] Preferably, the regulator for adjusting the pH of the iridium source solution includes aqueous ammonia.

[0024] Preferably, the temperature of the one-step heating treatment in step (2) is 40°C to 80°C, for example, 40°C, 50°C, 60°C, 70°C or 80°C, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the time for the one-step heating treatment in step (2) is 3 h to 8 h, for example, 3 h, 4 h, 5 h, 7 h or 8 h, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, stirring is performed during the one-step heating treatment in step (2).

[0027] Preferably, the stirring frequency of the one-step heating treatment in step (2) is 0.3 h / time to 0.8 h / time, for example: 0.3 h / time, 0.4 h / time, 0.5 h / time, 0.6 h / time, 0.7 h / time or 0.8 h / time, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the reducing agent solution in step (3) comprises sodium borohydride solution.

[0029] Preferably, the concentration of the sodium borohydride solution is 0.03 mol / L to 0.3 mol / L, for example, 0.03 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L or 0.3 mol / L, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the temperature of the second-step heating treatment in step (3) is 60°C to 90°C, for example, 60°C, 65°C, 70°C, 80°C or 90°C, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the time for the two-step heating treatment in step (3) is 6 h to 24 h, for example: 6 h, 8 h, 12 h, 18 h or 24 h, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, stirring is performed during the two-step heating treatment in step (3).

[0033] Preferably, the stirring frequency of the two-step heating treatment in step (3) is 0.8 h / time to 1.2 h / time, for example: 0.8 h / time, 0.9 h / time, 1 h / time, 1.1 h / time or 1.2 h / time, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] In a second aspect, the present invention provides an iridium catalyst composite proton membrane, which is prepared by the preparation method described in the first aspect.

[0035] Preferably, taking the mass of the iridium catalyst composite proton membrane as 100%, the mass fraction of the iridium catalyst is 30-55%, for example: 30%, 35%, 40%, 45%, 50% or 55%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In a third aspect, the present invention provides an electrolytic cell, comprising the iridium catalyst composite proton membrane as described in the second aspect.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention uses a simple method to in-situ prepare an iridium catalyst on the surface of the proton membrane. The iridium catalyst is tightly combined with the proton membrane, has high stability, and is not easy to fall off.

[0039] (2) The method described in the present invention successfully prepares the iridium catalyst in situ on the surface of the proton membrane to form an iridium catalyst composite proton membrane. The mass fraction of the iridium catalyst on the surface of the proton membrane can reach more than 12.5%, and the mass fraction of the iridium catalyst on the surface of the proton membrane can be controlled to be more than 47.8%. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041] Example 1

[0042] This embodiment provides an iridium catalyst composite proton membrane, and the iridium catalyst composite proton membrane is prepared by the following method:

[0043] The Nafion117 perfluorosulfonic acid proton exchange membrane was treated with hydrogen peroxide with a mass concentration of 5% and sulfuric acid with a concentration of 0.5 mol / L in sequence to obtain a pretreated proton membrane;

[0044] (2) mixing iridium trichloride and methanol to prepare an iridium trichloride solution with a concentration of 0.2 mol / L, adjusting the pH of the iridium trichloride solution to 10 with ammonia water, and placing it in an oven at 80° C., stirring once every 0.5 h, and reacting for 3 h to obtain a precursor;

[0045] (3) placing the precursor in a 0.3 mol / L sodium borohydride solution and then placing it in an oven at 90° C., stirring once every hour, and reacting for 6 hours to obtain the iridium catalyst composite proton membrane.

[0046] Example 2

[0047] This embodiment provides an iridium catalyst composite proton membrane, and the iridium catalyst composite proton membrane is prepared by the following method:

[0048] The Nafion117 perfluorosulfonic acid proton exchange membrane was treated with hydrogen peroxide with a mass concentration of 3% and sulfuric acid with a concentration of 0.2 mol / L in sequence to obtain a pretreated proton membrane;

[0049] (2) mixing iridium trichloride and methanol to prepare an iridium trichloride solution with a concentration of 0.15 mol / L, adjusting the pH of the iridium trichloride solution to 7 with ammonia water, and placing the solution in an oven at 80° C., stirring the solution every 0.3 h, and reacting the solution for 3 h to obtain a precursor;

[0050] (3) placing the precursor in a 0.03 mol / L sodium borohydride solution and then placing it in an oven at 60° C., stirring once every 1.2 hours, and reacting for 24 hours to obtain the iridium catalyst composite proton membrane.

[0051] Example 3

[0052] This embodiment provides an iridium catalyst composite proton membrane, and the iridium catalyst composite proton membrane is prepared by the following method:

[0053] The Nafion117 perfluorosulfonic acid proton exchange membrane was treated with hydrogen peroxide with a mass concentration of 8% and sulfuric acid with a concentration of 1 mol / L in sequence to obtain a pretreated proton membrane;

[0054] (2) mixing iridium trichloride and methanol to prepare an iridium trichloride solution with a concentration of 0.2 mol / L, adjusting the pH of the iridium trichloride solution to 10 with ammonia water, and placing it in an oven at 40° C., stirring it every 0.8 h, and reacting it for 8 h to obtain a precursor;

[0055] (3) placing the precursor in a 0.3 mol / L sodium borohydride solution and then placing it in an oven at 90° C., stirring once every 0.8 h, and reacting for 8 h to obtain the iridium catalyst composite proton membrane.

[0056] Example 4

[0057] The only difference between this embodiment and embodiment 1 is that the concentration of the iridium trichloride solution is 0.01 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0058] Example 5

[0059] The only difference between this embodiment and embodiment 1 is that the concentration of the iridium trichloride solution is 0.25 mol / L, and other conditions and parameters are exactly the same as those in embodiment 1.

[0060] Example 6

[0061] The only difference between this embodiment and embodiment 1 is that the pH of the iridium trichloride solution is 6, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0062] Example 7

[0063] The only difference between this embodiment and embodiment 1 is that the pH of the iridium trichloride solution is 11, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0064] Example 8

[0065] The only difference between this embodiment and embodiment 1 is that the temperature of the oven in step (2) is 30° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0066] Example 9

[0067] The only difference between this embodiment and embodiment 1 is that the temperature of the oven in step (2) is 100° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0068] Example 10

[0069] The only difference between this embodiment and embodiment 1 is that the concentration of the sodium borohydride solution is 0.02 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0070] Embodiment 11

[0071] The only difference between this embodiment and embodiment 1 is that the concentration of the sodium borohydride solution is 0.4 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0072] Example 12

[0073] The only difference between this embodiment and embodiment 1 is that the temperature of the oven in step (3) is 50° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0074] Example 13

[0075] The only difference between this embodiment and embodiment 1 is that the temperature of the oven in step (3) is 100° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0076] Comparative Example 1

[0077] The only difference between this comparative example and Example 1 is that no hydrogen peroxide treatment is performed, and other conditions and parameters are exactly the same as those in Example 1.

[0078] Comparative Example 2

[0079] The only difference between this comparative example and Example 1 is that sulfuric acid treatment is not performed, and other conditions and parameters are exactly the same as those in Example 1.

[0080] Comparative Example 3

[0081] The only difference between this comparative example and Example 1 is that the pH of the iridium trichloride solution is not adjusted, and the other conditions and parameters are exactly the same as those in Example 1.

[0082] The iridium catalyst composite proton membranes prepared in the examples and comparative examples were subjected to XRF detection, and the mass fraction of the iridium catalyst on the surface of the proton membrane is shown in Table 1:

[0083] Table 1

[0084] Iridium catalyst mass fraction (%) Example 1 54.5 Example 2 47.8 Example 3 52.6 Example 4 12.5 Example 5 54.3 Example 6 42.5 Example 7 53.8 Example 8 17.6 Example 9 54.2 Example 10 23.6 Embodiment 11 54.2 Example 12 36.7 Example 13 53.8 Comparative Example 1 3.2 Comparative Example 2 7.5 Comparative Example 3 1.2

[0085] As can be seen from Table 1, from Examples 1-13, the method of the present invention successfully prepares the iridium catalyst in situ on the surface of the proton membrane to form an iridium catalyst composite proton membrane, and the mass fraction of the iridium catalyst on the surface of the proton membrane can reach more than 12.5%, and the mass fraction of the iridium catalyst on the surface of the proton membrane can be controlled to be more than 47.8% by controlling the reaction conditions.

[0086] By comparing Example 1 with Examples 4-5, it can be seen that during the preparation process of the iridium catalyst composite proton membrane of the present invention, the concentration of the iridium trichloride solution will affect its performance. When the concentration of the iridium trichloride solution is controlled at 0.02-0.2 mol / L, the catalytic performance and stability of the iridium catalyst composite proton membrane obtained are good. If the concentration of the iridium trichloride solution is too high, the mass fraction of the iridium catalyst on the surface of the proton membrane does not increase significantly, but it will cause a waste of iridium and increase the cost. If the concentration of the iridium trichloride solution is too low, the mass fraction of the iridium catalyst on the surface of the proton membrane is too low, the iridium catalyst content in the composite proton membrane is too low, and the actual effect is poor.

[0087] By comparing Example 1 with Examples 6-7, it can be seen that during the preparation process of the iridium catalyst composite proton membrane of the present invention, the pH of the iridium trichloride solution will affect its performance. When the pH of the iridium trichloride solution is controlled at 7-10, the catalytic performance and stability of the iridium catalyst composite proton membrane are good. If the pH of the iridium trichloride solution is too high, the proton membrane will be partially denatured and the loading amount of the iridium catalyst will decrease. If the pH of the iridium trichloride solution is too low, the loading effect of the iridium catalyst will be greatly reduced.

[0088] By comparing Example 1 with Examples 8-9, it can be seen that in the preparation process of the iridium catalyst composite proton membrane of the present invention, the temperature of the one-step heating treatment in step (2) will affect its performance. When the temperature of the one-step heating treatment is controlled at 40-80°C, the catalytic performance and stability of the obtained iridium catalyst composite proton membrane are both good. If the temperature of the one-step heating treatment is too high, the reaction speed will not be further accelerated and resources will be wasted. If the temperature of the one-step heating treatment is too low, the reaction efficiency is low and an iridium catalyst composite proton membrane with good loading effect cannot be obtained in a short time.

[0089] By comparing Example 1 with Examples 10 to 11, it can be seen that in the preparation process of the iridium catalyst composite proton membrane of the present invention, the concentration of the sodium borohydride solution will affect its performance. When the concentration of the sodium borohydride solution is controlled at 0.03 to 0.3 mol / L, the catalytic performance and stability of the iridium catalyst composite proton membrane are good. If the concentration of the sodium borohydride solution is too high, the reaction time will not be further shortened, and the loading effect will not be further improved, but it will cause waste. If the concentration of the sodium borohydride solution is too low, the reaction speed is too slow, and it is difficult to obtain a good loading effect in a short time.

[0090] By comparing Example 1 with Examples 12 to 13, it can be seen that in the preparation process of the iridium catalyst composite proton membrane of the present invention, the temperature of the two-step heating treatment in step (3) will affect its performance. When the temperature of the one-step heating treatment is controlled at 60 to 90°C, the catalytic performance and stability of the iridium catalyst composite proton membrane obtained are good. If the temperature of the two-step heating treatment is too high, the reaction speed will not be further accelerated and resources will be wasted. If the temperature of the two-step heating treatment is too low, the reaction efficiency is low and an iridium catalyst composite proton membrane with good loading effect cannot be obtained in a short time.

[0091] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the present invention pre-treats the proton membrane with hydrogen peroxide and sulfuric acid to activate it, which can provide more attachment sites for iridium ions, so that the iridium ions are adsorbed on the surface of the proton membrane.

[0092] By comparing Example 1 and Comparative Example 3, it can be seen that after the pH of the iridium source solution is adjusted in the present invention, iridium ions can be better adsorbed on the surface of the proton membrane and will not be detached during the reduction process after the heat treatment, thereby greatly increasing the loading amount of the iridium catalyst on the proton membrane.

[0093] By comparing Example 1 and Comparative Example 4, it can be seen that after the proton membrane treated with hydrogen peroxide and sulfuric acid is placed in a configured iridium trichloride solution for reaction, the proton membrane reacted with the iridium trichloride solution is placed in a sodium borohydride solution, and an iridium catalyst is deposited in situ on the surface of the proton membrane. In the iridium catalyst composite proton membrane prepared by the method of the present invention, the iridium catalyst is formed in situ on the surface of the proton membrane, and the iridium catalyst is tightly combined with the proton membrane, is not easy to fall off, and has high stability.

[0094] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an iridium catalyst composite proton membrane, characterized in that: The preparation method comprises the following steps: (1) treating the proton membrane with hydrogen peroxide and sulfuric acid in sequence to obtain a pretreated proton membrane; (2) after adjusting the pH of the iridium source solution, mixing the pretreated proton membrane with the iridium source solution, and subjecting the mixture to a one-step heating treatment to obtain a precursor; (3) The precursor is mixed with a reducing agent solution, and subjected to a two-step heating treatment to obtain the iridium catalyst composite proton membrane.

2. The preparation method according to claim 1, characterized in that The proton membrane in step (1) comprises any one or a combination of at least two of a perfluorosulfonic acid proton exchange membrane, a Nafion recast membrane, a non-fluorinated polymer proton exchange membrane or a novel composite proton exchange membrane; Preferably, the mass concentration of the hydrogen peroxide in step (1) is 3% to 8%; Preferably, the concentration of sulfuric acid in step (1) is 0.2 mol / L to 1 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: The concentration of iridium ions in the iridium source solution of step (2) is 0.02 mol / L to 0.2 mol / L; Preferably, the solute of the iridium source solution in step (2) comprises iridium trichloride; Preferably, the solvent of the iridium source solution in step (2) comprises methanol and water; Preferably, the volume ratio of methanol to water is 1:(10-15); Preferably, the pH in step (2) is ≥ 7; Preferably, the regulator for adjusting the pH of the iridium source solution includes aqueous ammonia.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the one-step heating treatment in step (2) is 40°C to 80°C; Preferably, the heating treatment time in step (2) is 3 h to 8 h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Stirring during the one-step heating treatment in step (2); Preferably, the stirring frequency of the one-step heating treatment in step (2) is 0.3 h / time to 0.8 h / time.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The reducing agent solution in step (3) comprises a sodium borohydride solution; Preferably, the concentration of the sodium borohydride solution is 0.03 mol / L to 0.3 mol / L.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the second step heating treatment in step (3) is 60°C to 90°C; Preferably, the time for the two-step heating treatment in step (3) is 6 h to 24 h.

8. The preparation method according to any one of claims 1 to 4, characterized in that: Stirring during the two-step heating treatment in step (3); Preferably, the stirring frequency of the two-step heating treatment in step (3) is 0.8 h / time to 1.2 h / time.

9. An iridium catalyst composite proton membrane, characterized in that: The iridium catalyst composite proton membrane is prepared by the preparation method according to any one of claims 1 to 8; Preferably, based on the mass of the iridium catalyst composite proton membrane being 100%, the mass fraction of the iridium catalyst is 30-55%.

10. An electrolytic cell, characterized in that: The electrolyzer comprises the iridium catalyst composite proton membrane as claimed in claim 9.